Child road safety in transition: how economic growth shapes fatality risks for pedestrians, cyclists, and motorists - Law, Teik Hua; Yang, Kun; Zhu, Tong; Mohd Jakarni, Fauzan (Elsevier, 2025)
Child road safety is a major international concern, with traffic injuries being a top cause of child deaths. This study examines the connection between economic development and child road fatalities by travel mode to determine if the Kuznets curve—a phenomenon whereby fatalities first increase then decrease with economic development—exists for children. Based on 129-country (1990–2021) data stratified by the Inequality-adjusted Human Development Index (IHDI), the study applies fixed-effects negative binomial regression models to trends in pedestrian, cyclist, motorcyclist, and car occupant fatalities. The results demonstrate distinct and heterogeneous patterns across development levels. In low-IHDI countries, a U-shaped relationship emerges, where fatalities initially decrease but begin to rise again after a specific income threshold, with motorcycle risks resurging earliest. Medium-IHDI countries exhibit a consistent downward trend for most modes, reflecting the dominance of the abatement effect, though child motorcycle fatalities remain stubbornly persistent. Conversely, in high- and very high-IHDI countries, a classic inverse U-shaped Kuznets curve is confirmed. The steepness of the curve is manifested mainly in the case of cyclists and motorcyclists, evidencing their high sensitivity during the process of motorization, while the number of fatalities among car passengers exhibits a smoother trajectory with increased inherent safety standards of vehicles. This study challenges the assumption that economic growth guarantees road safety for children traveling in vehicles.